2020
DOI: 10.1038/s41467-020-19623-x
|View full text |Cite
|
Sign up to set email alerts
|

Associations between blood type and COVID-19 infection, intubation, and death

Abstract: The rapid global spread of the novel coronavirus SARS-CoV-2 has strained healthcare and testing resources, making the identification and prioritization of individuals most at-risk a critical challenge. Recent evidence suggests blood type may affect risk of severe COVID-19. Here, we use observational healthcare data on 14,112 individuals tested for SARS-CoV-2 with known blood type in the New York Presbyterian (NYP) hospital system to assess the association between ABO and Rh blood types and infection, intubatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

44
269
22
14

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 330 publications
(349 citation statements)
references
References 68 publications
44
269
22
14
Order By: Relevance
“…In the present study, there is an insignificant difference between the distribution of Rh type in both the control group and the COVID-19 group (p = 0.1913). Conversely, Zietz and Tatonetti [33] suggested a significant association between COVID-19 exposure and A and O blood groups with positive Rhesus factor (A+ and O+) solely.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In the present study, there is an insignificant difference between the distribution of Rh type in both the control group and the COVID-19 group (p = 0.1913). Conversely, Zietz and Tatonetti [33] suggested a significant association between COVID-19 exposure and A and O blood groups with positive Rhesus factor (A+ and O+) solely.…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, researchers from both China and USA reported that having type A blood is a high risk factor for COVID-19 infection, whereas having type O represents lower risk [13]. Zietz and Tatonetti [33] also reported negative harmonious relation between the O blood group and exposure to COVID-19. They did not recognize any significant association between blood group and either the need for intubation or COVID-19 related mortality, possibly due to their low size sample.…”
Section: Discussionmentioning
confidence: 96%
“…Studies from China and other parts of the world (USA, Turkey, Europe, Middle Eastern countries) have reported a relationship between the ABO blood group and the susceptibility to Covid-19. Despite some discrepancies, they showed a general trend that the risk of developing a SARS-CoV-2 infection was higher for individuals with type A blood and lower for those with type O blood ( Abdollahi et al, 2020 , Aljanobi et al, 2020 , Boudin et al, 2020 , Dzik et al, 2020 , Ellinghaus et al, 2020 , Gallian et al, 2020 , Göker et al, 2020 , Latz et al, 2020 , Leaf et al, 2020 , Li et al, 2020 , Shelton et al, 2020 , Valenti et al, 2020 , Wu et al, 2020 , Zeng et al, 2020 , Zhao et al, 2020 , Zietz et al, 2020 ). A similar lower risk for blood group O individuals had previously been observed in Hong Kong during the first major SARS outbreak, in 2003 ( Cheng et al, 2005 ).…”
Section: Introductionmentioning
confidence: 98%
“…It is now rather well documented through a large set of studies that blood group A individuals are at a higher risk of COVID-19 than individuals of blood group O, whilst blood group B seldom shows significant odd ratios relative to the other blood groups ( Aktimur et al, 2020 ; Barnkob et al, 2020 ; Chegni et al, 2020 ; Ellinghaus et al, 2020 ; Göker et al, 2020 ; Latz et al, 2020 ; Leaf et al, 2020 ; Li et al, 2020 ; Muniz-Diaz et al, 2020 ; Shelton et al, 2020 ; Sohlpour et al, 2020 ; Valenti et al, 2020 ; Wu et al, 2020 ; Zeng et al, 2020 ; Zhang et al, 2020 ; Zhao J. et al, 2020 ; Zietz et al, 2020 ). We recently observed that anti-A and anti-B agglutinating natural antibodies were significantly lower in COVID-19 patients compared with controls ( Deleers et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, group O individuals possess anti-A and anti-B antibodies that could have protected them from viral particles emitted by either blood group A or B patients. Interestingly, a large number of observations indicate that blood group O individuals have a lower risk of COVID-19, whereas blood group A individuals appear to be at a higher risk ( Cheng et al, 2005 ; Abdollahi et al, 2020 ; Ahmed et al, 2020 ; Aljanobi et al, 2020 ; Barnkob et al, 2020 ; Chegni et al, 2020 ; Delanghe et al, 2020 ; Dzik et al, 2020 ; Ellinghaus et al, 2020 ; Fan et al, 2020 ; Franchini et al, 2020 ; Gallian et al, 2020 ; Göker et al, 2020 ; Hoiland et al, 2020 ; Latz et al, 2020 ; Leaf et al, 2020 ; Li et al, 2020 ; Muniz-Diaz et al, 2020 ; Niles et al, 2020 ; Padhi et al, 2020 ; Ray et al, 2020 ; Roberts et al, 2020 ; Shelton et al, 2020 ; Sohlpour et al, 2020 ; Valenti et al, 2020 ; Wu et al, 2020 ; Zeng et al, 2020 ; Zhang et al, 2020 ; Zhao J. et al, 2020 ; Zietz et al, 2020 ). Only a few studies failed to find any association between ABO types and COVID-19, likely depending on study design ( Boudin et al, 2020 ; Focosi et al, 2020 ; Pairo-Castineira et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%